Persepsi Publik Terhadap Pengelolaan Lingkungan Hidup di Wilayah Jayapura–Papua - Puguh Sujarta; Suharno Suharno; Farmawaty Farmawaty; Leonardo A. Numberi; Irma Rahayu; Marseline G. Mailisa; Irene Suebu; Roma M. Manalu; Wehelmina Lahallo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Papua has a huge diversity of natural resources which can be categorized as well managed compare to other areas in Indonesia. The city of Jayapura and its surrounding are arranged to become an urban area nowadays. As an impact, many sector has changing including its land use. This research aims to understanding the knowledge, perception, and assesment of people regarding the environment particularly in Jayapura and its environs. The research was conducted in Jayapura City, Jayapura Regency and Keerom Regency with sampling method using survey, questionnaire and documentation. This research revealed that 53.0–90.0% of respondent knowing about environmental management and most of them (90.0%) gained those information from educational institution such as schools. Regarding government participation in environmental management, respondent answered that it is around 69.0–76.0% while for infrastructure and monitoring it is around 52.4-74.0% and 41.0-70.6% respectively. Concerning the environmental condition and its management the rate was 6.20 which can be categoized as good.Key words: people perception; environment; government; Jayapura.